2021
DOI: 10.1038/s41598-021-90919-8
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury molecule-1 inhibits metastasis of renal cell carcinoma

Abstract: Metastasis is present in approximately 30% of patients diagnosed with renal cell carcinoma (RCC) and is associated with a 5-year survival rate of < 15%. Kidney injury molecule 1 (KIM-1), encoded by the HAVCR1 gene, is a proximal tubule cell-surface glycoprotein and a biomarker for early detection of RCC, but its pathophysiological significance in RCC remains unclear. We generated human and murine RCC cell lines either expressing or lacking KIM-1, respectively, and compared their growth and metastatic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…KIM1, a type-I cell surface glycoprotein, negatively correlated with creatinine. As an acute marker of early acute kidney injury, KIM1 is predictive of long-term renal outcome [97] and is reported to have protective functions in renal ischemia-reperfusion injury, promote renal graft recovery, have a role in renal cancer pathophysiology and serve as a biomarker for sepsis-induced acute kidney injury [98][99][100][101][102]. The tumor necrosis and transforming growth factor protein families have well-known roles in cellular migration, growth, differentiation, and tissue repair [103], as well as critical roles in mediating the cytokine storm in sepsis [104].…”
Section: Discussionmentioning
confidence: 99%
“…KIM1, a type-I cell surface glycoprotein, negatively correlated with creatinine. As an acute marker of early acute kidney injury, KIM1 is predictive of long-term renal outcome [97] and is reported to have protective functions in renal ischemia-reperfusion injury, promote renal graft recovery, have a role in renal cancer pathophysiology and serve as a biomarker for sepsis-induced acute kidney injury [98][99][100][101][102]. The tumor necrosis and transforming growth factor protein families have well-known roles in cellular migration, growth, differentiation, and tissue repair [103], as well as critical roles in mediating the cytokine storm in sepsis [104].…”
Section: Discussionmentioning
confidence: 99%
“…The innovation of gene editing technologies has significantly reduced the time needed to establish a GEMM ( 34 ). GEMM has been used in the study of colorectal cancer ( 35 ), renal cell carcinoma ( 36 ) and breast cancer ( 37 ). In addition, it can be used in preclinical trials for hormonal and targeted therapies as well as immunotherapy.…”
Section: Tumor Mouse Modelmentioning
confidence: 99%
“…The time to metastatic relapse is variable, usually several years after surgical treatment. Our case report has an early filing of 4 months, which is below the average (24 months) in a series of cases [1] and for other case reports [2,[7][8][9], also the initial size of the mass is unusual with a commitment of 100% of the lumen, which is greater than the reported cases, where a solitary nodule or polyp is generally reported that does not occupy the entire esophageal diameter [2,9,10], the treatment is multidisciplinary, with surgical treatment as the first option and a combination of radiotherapy and chemotherapy [8,9], with the increasingly widespread use of tyrosine kinase inhibitors such as pazopanib [2][3][4][5][6], or checkpoint inhibitors.…”
Section: Ccrc: Clear Cell Renal Cell Carcinomamentioning
confidence: 99%
“…The metastases secondary to clear cell renal cell carcinomas (CCRC) are present in approximately 30% of patients with advanced stages and this is associated with <15% 5-year survival [ 3 ]. The most common sites of metastasis are the lungs (70%) and bone (32%), on the other hand, the less frequent metastases are thyroid (0.7%) and gastric (0-7%), which represent <5% of the metastases of CCR [ 4 - 5 ].…”
Section: Introductionmentioning
confidence: 99%